2019
DOI: 10.1111/ijsa.12263
|View full text |Cite
|
Sign up to set email alerts
|

Does interview anxiety predict job performance and does it influence the predictive validity of interviews?

Abstract: Interview anxiety is negatively related to interview performance; however, its relation to job performance is unknown. It could correlate negatively with job performance, and it could moderate the interview performance–job performance relation. In a sample of applicants for Residence Assistant positions, interview anxiety had near‐zero correlations with job performance, rated by supervisors and supervisees. It moderated the relation between interview performance and supervisor‐rated facilitating peer and team … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…This design feature ensured that there was a diverse array of jobs and industries to test whether work-related anxieties affect job performance, and whether this relation is moderated by the social-evaluative job content with the added benefit of using a common measure of job performance across all jobs and industries. In doing so, this study extended past study designs by Schneider et al (2019) (Powell et al, 2018). The interview context might be challenging for some older adults who are newly on the job market (e.g., after experiencing job loss; Wanberg et al, 2016).…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 94%
See 2 more Smart Citations
“…This design feature ensured that there was a diverse array of jobs and industries to test whether work-related anxieties affect job performance, and whether this relation is moderated by the social-evaluative job content with the added benefit of using a common measure of job performance across all jobs and industries. In doing so, this study extended past study designs by Schneider et al (2019) (Powell et al, 2018). The interview context might be challenging for some older adults who are newly on the job market (e.g., after experiencing job loss; Wanberg et al, 2016).…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 94%
“…In doing so, this study makes both theoretical and practical contributions. Specifically, we seek to replicate, extend, and explain a pattern of recent results that found a null relationship between interview anxiety and later job performance (Schneider et al, 2019; Voyles, 2019). Whereas these recent studies focused on one specific real or simulated job, in the current study we look at a variety of jobs from different industries, and we investigate whether the type of work environment moderates the relation between interview anxiety and job performance.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…To be specific, studies have found that interviewees experiencing anxiety during an interview receive lower ratings of performance and are less likely to be hired for the position (see Powell et al, 2018). This finding is troublesome given that no existing research has demonstrated that anxious interviewees are less suitable for the job; rather, there is one study that found that the job interview exhibited lower predictive validity of job performance in highly anxious students who were applying for University-based residence positions (Schneider et al, 2019). While these studies are informative, the majority have been based on mock interviews or are focused on students applying for jobs through University career counseling services (see Powell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…
Employment interview still gathers elevated scholarly attention, as it represents the most popular selection tool among employers (Macan, 2009;McCarthy & Cheng, 2018), and it is seen favorably by applicants (Anderson et al, 2010). Scholars have been increasingly studying the employment interview from the applicants' perspective (McCharty & Cheng, 2014), focusing on their attitudes, self-cognitions, and emotions, and evaluating the impact of these aspects on their performance (see Nikolaou & Georgiou, 2018;Schneider et al, 2019).We aim at strengthening understanding of interview selfefficacy (henceforth, ISE), a prominent self-cognition explaining employment interview performance (Tay et al, 2006;Tross &
…”
mentioning
confidence: 99%